Avaliação da atividade antibacteriana in vitro de extratos vegetais e geoprópolis de Melipona sp. sobre Aeromonas hydrophila e Staphylococcus aureus - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Infectious diseases are responsible for high mortality is a problem for public and animal health. Due to these problems, the use of chemotherapy is recurrent in fish therapy. Given the risks associated with classically used health control methods in fish farming, an alternative would be the use of herbal medicines. This study aims to evaluate the antibacterial action of plant extracts and geopropolis of Melipona sp. against Aeromonas hydrophila and Staphylococcus aureus bacteria. The extracts were divided into: A1 (Heated aqueous extract of Annona squamosa peel 50mg / mL); A2 (Unheated aqueous extract of Annona squamosa leaves 50mg / mL); A3 (Annona squamosa 50mg / mL heated leaf extract); B1 (heated aqueous extract of Vouacapoua americana 65 mg / mL); B2 (50% hydroxyanolic extract of Vouacapoua americana 65 mg / mL); B3 (100% Vouacapoua americana ethanolic extract 65 mg / mL); C1 (hydroethanolic extract 50% of the leaves of Pouteria macrophylla 50 mg / mL); and D1 (Geopropolis Extract 50 mg / mL). The extracts were tested against gram positive bacteria S. aureus ATCC 14458 and gram negative A. hydrophila - isolated from infected fish. The study was conducted at the Microbiology Laboratory, Federal University of Western Pará - UFOPA. The determination of in vitro antimicrobial activity followed the descriptions of protocol M02-A12 of the Clinical and Laboratory Standards Institute (CLSI, 2015) using the disk diffusion test described by Kirb and Bauer. The leaves extract of Pouteria macrophylla 50 mg / mL and the 100% ethanol extract of Vouacapoua americana 65 mg / mL showed inhibition of S. aureus growth. Both had halos measuring 7mm in diameter. None of the extracts showed inhibitory action against growth of A. hydrophila. However, these activities did not show significant action on the strains. It was concluded that in higher concentrations or with the aid of another methodology, the hydroethanolic extract of cutite (Pouteria macrophylla) and the ethanolic extract of acapu (Vouacapoua americana) may have higher antimicrobial activity. Further and further studies, such as toxicity, are required for commercial use of these species in aquaculture.
Keywords: Piscicultura; Extratos; Antibiograma; CNPQ:: CIÊNCIAS AGRÁRIAS